Diamonds, gold and crime displacement: Hatton Garden, and the evolution of organised crime in the UK - Lashmar, Paul (Trends in organized crime, 2018)
The 2015 Hatton Garden Heist was described as the ‘largest burglary in English legal history’. However, the global attention that this spectacular crime attracted to ‘The Garden’ tended to concentrate upon the value of the stolen goods and the vintage of the burglars. What has been ignored is how the burglary shone a spotlight into Hatton Garden itself, as an area with a unique ‘upperworld’ commercial profile and skills cluster that we identify as an incubator and facilitator for organised crime. The Garden is the UK’s foremost jewellery production and retail centre and this paper seeks to explore how Hatton Garden’s businesses integrated with a fluid criminal population to transition, through hosting lucrative (and bureaucratically complex) VAT gold frauds from 1980 to the early 1990s, to become a major base for sophisticated acquisitive criminal activities. Based on extensive interviews over a thirty year period, evidence from a personal research archive and public records, this paper details a cultural community with a unique criminal profile due to the particularities of its geographical location, ethnic composition, trading culture, skills base and international connections. The processes and structures that facilitate criminal markets are largely under- researched (Antonopoulos et al. 2015: 11), and this paper considers how elements of Hatton Garden’s ‘upperworld’ businesses integrated with project criminals, displaced by policing strategies, to effect this transition.